Revisiting the Entrainment Relationship of Convective Plumes: A Perspective From Global Observations. Issue 6 (22nd March 2021) - Takahashi, Hanii; Luo, Zhengzhao Johnny; Stephens, Graeme
Abstract: Entrainment is an important process affecting convective transport and is a key parameter in convection modeling. For over half a century, an inverse relationship between entrainment rate ( λ ) and convective core size ( R ) has been used in modeling convective clouds. This short letter revisits the λ ‐ R relation using multiple years of CloudSat observations. Results show that the inverse relationship between λ and R is robust. However, they are not scaled by a simple constant. Global satellite observations provide some guidance for choosing the range of the scaling parameter. Further, our analysis shows that continental convective clouds tend to have smaller λ and larger R compared to oceanic convective clouds, suggesting that vertical mass transport by continental convection is more efficient. The satellite‐based study of the λ ‐ R relation has the potential to become a new diagnostic metric for assessing the representation of convection in weather and climate models. Plain Language Summary: Convection is a key component of Earth's climate system making complex couplings among radiative, thermodynamic, and dynamic processes of the system. Properly modeling and representing convection has long been a central task of weather and climate models. Among various processes associated with convection, entrainment of the ambient air plays a critical role as it dilutes the strength of vertical transport by convection. For over half a century, an inverse relationship between entrainment rate ( λ ) and convective core size ( R ) has been used in modeling convective clouds. The purpose of this study is to revisit the λ ‐ R relation using multiple years of CloudSat observations. Our results show that the inverse relationship is robust. However, they are not scaled by a simple constant. Global satellite observations provide some guidance for choosing the range of the scaling parameter. Further, our analysis shows that continental convective clouds tend to have smaller λ and larger R compared to oceanic convective clouds, suggesting that vertical mass transport by continental convection is more efficient. Finally, we point out that this satellite‐based study of the λ ‐ R relation has the potential to become a new diagnostic metric for assessing the representation of convection in weather and climate models. Key Points: For over half a century, an inverse relationship between entrainment rate and convection size has been used in convection modeling This study revisits the entrainment rate ( λ )‐convective core size ( R ) relation using multiple years of global satellite observations Results support the λ ‐ R relation and provide more details including the value of the scaling parameter and land‐ocean differences